Climate Change Will Fragment Florida Stone Crab Communities - Alaerts, Lauranne; Dobbelaere, Thomas; Gravinese, Philip M.; Hanert, Emmanuel (Frontiers in Marine Science, 2022)
The tolerance of many marine species is being threatened by both ocean acidification and ocean warming which are reducing survival, altering behavior, and posing limits on physiology, specially during earlier life stages. The commercially important Florida stone crab, Menippe mercenaria, is one species that is affected by changes in seawater pH and temperature. In this study, we determined the impacts of reduced pH and elevated temperature on the distribution of the stone crab larvae along the West Florida Shelf. To understand the dispersion of the larvae, we coupled the multi-scale ocean model SLIM with a larval dispersal model. We then conducted a connectivity study and evaluated the impacts of climate change by looking at three different scenarios which included models that represented the dispersion of stone crab larvae under: 1) present day conditions (pH = 8.0), 2) moderate pH (-0.275 reduction in pH) and temperature changes (+ 1 °C), and 3) extreme pH (-0.43 reduction in pH) and temperature conditions (+3 °C). Our results show a clear impact of these climate change stressors on larval dispersal and on the subsequent stone crab distribution. Future climate change could result in stone crabs moving north or into deeper waters. We also observed an increase in the number of larvae settling in deeper waters (defined as the non-fishing zone in this study with depths exceeding 30 m) that are not typically part of the commercial fishing zone. The distance travelled by larvae, however, is likely to decrease, resulting in an increase of self-recruitment and decrease of the size of the sub-populations. Our results suggest that habitats in the non-fishing zone cannot serve as a significant source of larvae for the habitats in the fishing zone (defined as water depth < 30 m) since there is very little exchange (< 5% of all exchanges) between the two zones. These results indicate that the stone crab populations in Florida may be susceptible to community fragmentation and that the management of the fishery should consider the potential impacts of future climate change scenarios.